Energy, exergy, and advanced exergy analysis of a novel solar-based S-CO2 cycle and comparison of systems with different layouts - Qiujie Cheng; Yunlong Zhou; Mei Yang; Xinrui Han; Jiani Liu (Case Studies in Thermal Engineering)
Solar energy is an endless source of renewable energy, so solar-powered S-CO2 cycle power generation systems have received much attention from scholars. In this research, a new S-CO2 cycle layout based on a recompression cycle and an intercooling cycle is proposed, and the thermal performance of the three layouts is compared and analyzed. Percentage exergy loss of each component in the system is obtained by conventional exergy analysis and further advanced exergy analysis is used to explore the enhancement possibilities of each component and their interactions. The investigation results revealed that the recompression cycle, intercooling cycle and combined cycle had respective evaluations of 38.45 %, 39.775 and 42.05 % efficiency. Sensitivity analysis revealed that the provided cycle has superior efficiency at higher turbine inlet parameters. The conventional exergy analysis and advanced exergy analysis yielded a combined cycle HE1 exergy loss of 8.27 MW and an avoidable exergy loss of 4.70 MW, with a high potential for improvement. This study provides directions for the structural optimization of solar-driven S-CO2 cycle power generation systems.